The Effect of Wharton’s Jelly Mesenchymal Stem Cells on Nestin Gene Expression in Alzheimer's Rat Models - Annita Annita; Arniat Christiani Telaumbanua; Yanti Rahayu; Putri Dafriani; Hendri Panus (Jurnal Kesehatan Saintika Meditory, 2026)
Alzheimer's disease (AD) is characterized by neurodegeneration and decreased neurogenesis due to neuroinflammation and free radical accumulation. Nestin is an intermediate filament protein that serves as a primary marker for neural progenitor cells in the neurogenesis process. This study aimed to analyze the effect of Wharton’s Jelly Mesenchymal Stem Cells (WJ-MSCs) administration on Nestin gene expression in an Alzheimer's rat model. This experimental study with a posttest-only control group design utilized male white rats (Rattus norvegicus) induced by Aluminum chloride (AlCl3) at a dose of 300 mg/kg BW orally for 5 days to model Alzheimer's pathology. A dose of 1×106 WJ-MSCs was injected intraperitoneally in the treatment group. One month post-therapy, Nestin gene expression from brain tissue was analyzed using quantitative Real-Time Polymerase Chain Reaction (qRT-PCR) and statistically tested with One-Way ANOVA. The results showed a statistically significant difference (p < 0.05), with a significant increase in Nestin gene expression in the WJ-MSCs treated group compared to the positive control group. It is concluded that the administration of WJ-MSCs effectively increases Nestin gene expression, indicating an improvement in the regeneration and neurogenesis processes in the brain tissue of Alzheimer's rat models.